2018
DOI: 10.1002/jcc.25570
|View full text |Cite
|
Sign up to set email alerts
|

Systematic High‐Accuracy Prediction of Electron Affinities for Biological Quinones

Abstract: Quinones play vital roles as electron carriers in fundamental biological processes; therefore, the ability to accurately predict their electron affinities is crucial for understanding their properties and function. The increasing availability of cost-effective implementations of correlated wave function methods for both closed-shell and open-shell systems offers an alternative to density functional theory approaches that have traditionally dominated the field despite their shortcomings. Here, we define a bench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 149 publications
(175 reference statements)
2
6
0
Order By: Relevance
“…Similar conclusions hold for the state‐specific PNO implementation as well as for the state averaged PNO EOM implementation of Valeev . Our own STEOM implementation depends on ground state PNOs, for which standardized parameter sets guaranteeing a certain accuracy are available, and it has been shown that the error in the ground state computation and in the subsequent IP/EA calculations can also be kept below similar limits . The question of accuracy is most complicated for multilayer embedding methods.…”
Section: Benchmarkssupporting
confidence: 65%
See 1 more Smart Citation
“…Similar conclusions hold for the state‐specific PNO implementation as well as for the state averaged PNO EOM implementation of Valeev . Our own STEOM implementation depends on ground state PNOs, for which standardized parameter sets guaranteeing a certain accuracy are available, and it has been shown that the error in the ground state computation and in the subsequent IP/EA calculations can also be kept below similar limits . The question of accuracy is most complicated for multilayer embedding methods.…”
Section: Benchmarkssupporting
confidence: 65%
“…121 Our own STEOM implementation depends on ground state PNOs, for which standardized parameter sets guaranteeing a certain accuracy are available, 205 and it has been shown that the error in the ground state computation and in the subsequent IP/EA calculations can also be kept below similar limits. 74,[132][133][134]206 The question of accuracy is most complicated for multilayer embedding methods. Here, the size of the various layers and whether the excitation crosses the layer boundaries are the factors that determine accuracy.…”
Section: Valencementioning
confidence: 99%
“…For this reason, the T CutPNOSingles threshold plays a crucial role in determining the accuracy of the method. More information on the equations can be found in the literature. , As the active space selection is also in the canonical basis, the constructed unit vector guess can be used directly without further transformation.…”
Section: Theoretical Aspects and Computational Detailsmentioning
confidence: 99%
“…The terpenoids are easily reduced to diphenol derivatives, 16 which are then oxidized 17 and easily converted. 18 Quinone compounds play a role in the transmission of electrons, 19 as a product of metabolism of organisms, 20,21 exhibits a variety of biological activities by promoting or interfering with various biochemical reactions of organisms, 22 and promotes certain biochemical reactions as coenzymes 23 for biological reactions. 22 Or interfere with the action, 24 thus showing a variety of pharmacological effects, such as anti-atherosclerosis, 25 anti-myocardial ischemia, 26 anti-arrhythmia, 27 repair of vascular endothelial cells, 28 improve coronary blood circulation, 29 anticardiac hypertrophy, and anti-tumor (as shown in Figure 2).…”
Section: Introductionmentioning
confidence: 99%